ETHNOBOTANICAL STUDY IN TOLEDO-PR DISTRICT: AN APPROACH ABOUT USED SPECIES VARIABILITY WITH THE SAME POPULAR NAME - HOLZBACH, J. C.; HOLZBACH, L. C.; OLGUIN, C. F. A. (Visão Acadêmica, 2016)
The ethnopharmacological knowledge acquired throughout human evolution culminated in the development of high therapeutic relevance drugs. In ethnobotanical survey conducted in the city of Toledo in 2007, it was found that 79% of the population often use plants for medicinal purposes, mostly in the tea form, originated from own crops. They claimed that the consumption of these plants improved their health conditions. The plants mainly cited were: balm, chamomile and marcela. This study aimed to verify if the population habits related to medicinal plants have changed, also proceed a literature review to find out if the most used plants have their biological activity scientifically proven and looking for reports of homonymous to the most cited medicinal plants. There was small change in the species used by the population. In the literature, it was found out that different species are used with the same popular name, in practice, it was detected the use of two different species, Piper amalago L. (UNOP 7972) and Piper mikanianum (Kunth) (UNOP 7971), for the medicinal plant commonly known as pariparoba, although none of them is recognized for the Brazilian Pharmacopoeia.